Pendidikan Akhlak Anak Dalam Perspektif Abdulah Nasih Ulwan dan Relevansinya dengan kondisi saat ini - Erfa Ernawati (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of national education is to develop the potential of learners to become human beings who believe and cautious to God Almighty, have noble character, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible. In fact, although the number of educated people is increasing, there is still a lot of criminality, immorality, violation of law and other issues as if eliminating the identity of a nation that berpencasila. This is where the importance of morals, the role of morals in life is often beyond the role of science, for science without morality encourages people to the kebiadapan